Leishmania tropica: Another Etiological Agent of Canine Visceral Leishmaniasis in Iran. - H Hajjaran; M Mohebali; Z Zarei; GhH Edrissian (Tehran University of Medical Sciences, 2007)
Background: Dogs have been previously reported to be reservoirs of Leishmania infantum as the etiological agent of human visceral leishmaniasis in Iran. We report a case of canine visceral leishmaniasis (VL) caused by L. tropica from the north- west of Iran where human visceral leishmaniasis is endemic. Methods: The canine VL was initially screened by dipstick rK39 and direct agglutination test, then the dog was dissected and obtained samples were examined by parasitological (direct exam, cultivation) and molecular techniques (RAPD-PCR and RFLP-PCR). Results: Leishmania parasites were found in spleen and liver of the dog. The serological tests for the detection of specific anti-leishmania antibodies showed positive results. Conclusion: L. tropica as another agent of canine VL was determined.